Kv7.4 Channel Contribute to Projection-Specific Auto-Inhibition of Dopamine Neurons in the Ventral Tegmental Area - Su, Min; Li, Li; Wang, Jing; Sun, Hui; Zhang, Ludi; Zhao, Chen; Xie, Ying; Gamper, Nikita; Du, Xiaona; Zhang, Hailin (Frontiers in Cellular Neuroscience, 2019)
Dopaminergic neurons in ventral tegmental area (VTA) encode behavioural patterns important in reward and drug addiction as well as in emotional disorders. These functions of dopamine neurons are directly related to the release of dopamine in the targeted regions of brain which are, thus, controlled by the excitability of dopamine neurons. One mechanism for modulation of dopamine neuronal excitability is mediated by the auto dopamine type 2 (D2) receptors, through activation of a Kir3/GIRK K+ channel which inhibits the firing of dopamine neurons. In this study, we provide evidence that Kv7.4, in addition to Kir3.2 channels, contributes to DA-mediated auto-inhibition of DA activity projecting to NAc and to BLA. Furthermore we demonstrate that D2 receptors enhance Kv7.4 currents through Gi/o protein and redox-dependent cellular pathway. Finally, we show this D2 mediated auto-inhibition is blunted in a social defeat mice model of depression, a phenomenon that may contribute to the altered excitability of VTA DA neurons in depressed animals. These results provide a new perspective for understanding molecular mechanism of excitability of VTA DA neurons and for potential new strategies against mental disorders involving altered excitability of DA neurons, such as major depression and drug addictions.